2008
DOI: 10.1590/s0004-27302008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Gasto energético corporal: conceitos, formas de avaliação e sua relação com a obesidade

Abstract: ABE&M todos os direitos reservados RESUMOA obesidade, apesar de intensamente estudada nos últimos anos, ainda apresenta muitas controvérsias, entre elas a sua relação com o gasto energético (GE). O presente estudo representa uma revisão da literatura procurando abordar: as técnicas existentes para avaliação do GE, com suas vantagens e limitações e as relações existentes entre GE e a obesidade. O GE pode ser avaliado por métodos calorimé-tricos, espectrométricos, ou mesmo por questionários. De acordo com os obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
0
10
0
12
Order By: Relevance
“…However, this increase may be due to increased basal metabolic rate (BMR) due to higher fat-free mass (FFM) and energy demand during physical activity. However, Melo et al [3] found that obese individuals are economical, the metabolic point of view. Therefore, the energy expenditure (EE) per kilogram of body weight at the give time is lower in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, this increase may be due to increased basal metabolic rate (BMR) due to higher fat-free mass (FFM) and energy demand during physical activity. However, Melo et al [3] found that obese individuals are economical, the metabolic point of view. Therefore, the energy expenditure (EE) per kilogram of body weight at the give time is lower in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Homeostasis is one of the greatest challenges for understanding the etiology, treatment and prevention of obesity (Hill, 2006). The high rate of weight regain in individuals who undergo weight loss treatments is proof of this (Melo et al, 2008). Even among morbidly obese individuals submitted to more radical treatments, such as surgery, weight regain sometimes occurs [Fogaça, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…É uma doença de origem multifatorial, abrangendo fatores genéticos, metabólicos, fisiológicos ou ainda relacionados ao estilo de vida. No que diz respeito a aspectos fisiológicos e metabólicos, estudos têm procurado identificar se o gasto energético em repouso ou em resposta à prática de atividade física está reduzido em obesos, colaborando com o ganho de peso corporal (3) . Considerando o aumento da incidência de obesidade em adolescentes, é importante que se conheça com mais profundidade alguns fatores associados a esse desvio nutricional.…”
Section: Introductionunclassified